2018
DOI: 10.5535/arm.2018.42.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Motor and Sensory Function as a Predictor of Respiratory Function Associated With Ventilator Weaning After High Cervical Cord Injury

Abstract: Objective To analyze the respiratory function of high cervical cord injury according to ventilator dependence and to examine the correlations between diaphragm movement found on fluoroscopy and sensory and motor functions.MethodsA total of 67 patients with high cervical spinal cord injury (SCI), admitted to our hospital were enrolled in the study. One rehabilitation physician performed sensory and motor examinations on all patients while each patient was in the supine position on the American Spinal Injury Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Twenty-five studies were run in ICUs [ 12 , 30 33 , 35 – 44 , 46 , 57 , 59 62 , 64 66 ], 14 in rehabilitative settings [ 34 , 45 , 47 56 , 58 , 61 ] (Additional file 1 : Table S1). In 8 studies the cause of the injury was not specified [ 33 , 43 , 47 , 49 , 51 , 53 , 54 , 58 ], all the remaining studies enrolled traumatic SCI patients, 2 of them [ 55 , 61 ] enrolled both traumatic and a few non-traumatic patients, whose outcomes were not separable. Among the studies focusing on traumatic SCI, 6 excluded patients with concomitant traumatic brain injury [ 30 , 32 , 40 , 60 , 62 , 66 ], 1 excluded patients with multiple spinal cord lesions [ 65 ] and 1 excluded patients with concomitant extra-spine lesions [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five studies were run in ICUs [ 12 , 30 33 , 35 – 44 , 46 , 57 , 59 62 , 64 66 ], 14 in rehabilitative settings [ 34 , 45 , 47 56 , 58 , 61 ] (Additional file 1 : Table S1). In 8 studies the cause of the injury was not specified [ 33 , 43 , 47 , 49 , 51 , 53 , 54 , 58 ], all the remaining studies enrolled traumatic SCI patients, 2 of them [ 55 , 61 ] enrolled both traumatic and a few non-traumatic patients, whose outcomes were not separable. Among the studies focusing on traumatic SCI, 6 excluded patients with concomitant traumatic brain injury [ 30 , 32 , 40 , 60 , 62 , 66 ], 1 excluded patients with multiple spinal cord lesions [ 65 ] and 1 excluded patients with concomitant extra-spine lesions [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies provided no definition of weaning success/failure, and studies that reported it widely differed in their criteria; when the definition of partial weaning was provided, analogous variability was also present (Additional file 1 : Table S5). The majority of the studies did not mention the use of any weaning protocol [ 8 , 12 , 31 , 33 , 34 , 42 , 47 , 49 , 52 , 57 , 61 ]; two studies mentioned the use of a protocol without specifying it [ 48 , 64 ]. For the remaining 10 studies, the most frequently weaning protocol was a progressive increase in ventilator-free breathing, with mild variations among the studies, including unassisted breathing until tired or graded time off the ventilator [ 45 , 50 , 58 , 65 ]; unassisted breathing alternated to periods of intermittent mandatory ventilation, continuous positive airway pressure [ 43 ] or pressure support ventilation [ 46 , 51 , 56 ]; non-invasive ventilation with the tracheostomy sealed [ 53 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although only a few specific weaning strategies have been studied, there is some recent literature pertaining to identification of patients who can be weaned from mechanical ventilation or decannulated. Patients who can be weaned tend to be able to shrug their shoulder within 3 weeks of injury, have higher vital capacities, have higher forced vital capacities, higher maximal inspiratory pressures, and lower spinal level of injury [ 13 , 31 , 43 ]. Patients who could not be weaned, or had more difficulty being weaned, were over the age of 56, had injuries at C4 or higher, had a vital capacity less than 1500, had a BMI above 25, and had chronic obstructive pulmonary disease [ 32 ].…”
Section: Ventilator Weaning Strategiesmentioning
confidence: 99%